Building a Sustainable Campus: A Study of Green Campus Implementation at Kuningan University - Hadziq Asyraf Dwi Ananda; Siska Aulia Hikmah; Tanti Oktavianti; Agnesia Tri Puspita Sari; Rani Tania (Yayasan Dekhalisha Global Prestise, 2026)
The implementation of the green campus concept in higher education institutions is crucial for achieving Sustainable Development Goals (SDGs), particularly SDG 11 (Sustainable Cities and Communities) and SDG 13 (Climate Action). This study evaluates the implementation of the green campus concept at Kuningan University (UNIKU) through a mixed-method approach. Data were collected through observations, interviews with university management, and questionnaires distributed to 100 students. The results indicate that UNIKU has implemented several green campus initiatives, including waste management systems, energy efficiency programs, and green infrastructure development. However, challenges persist, including limited student participation (only 30% actively involved), inadequate maintenance of open spaces, and the absence of an integrated waste management system. The study reveals that 80% of students are aware of green campus efforts, yet 60% lack knowledge about specific environmental activities organized by the university. This research contributes to understanding the barriers and enablers of green campus implementation in Indonesian higher education institutions and provides recommendations for enhancing sustainability practices through the 5P movement (Perawatan, Pemeliharaan, Pengurangan, Pengelolaan, dan Pendidikan).